The platform review alliance board: Designing an organizational model to bring together producers and consumers in the review and commissioning of platform software - Justin Larner; Åke Walldius (Journal of Organization Design, 2019)
Digital networking technology has helped to bring about the platform economy, in which online networking sites mediate between individual freelance workers and their temporary employers. However, the digital platform economy undermines traditional forms of collective action, particularly trade unions. Following reflections on 15 years of trade union software quality assurance initiatives, particularly the Swedish UserAward program, we realize that there are potential benefits in combining aspects of cooperative, guild, and trade union models in the context of the platform economy. We examine the role that these models could play in enabling new forms of collective action and we bring them together in the form of a conceptual model which we have called the Platform Review Alliance Board. We articulate the Platform Review Alliance model as a set of design patterns, which we invite stakeholders to comment on, refine, and ultimately subscribe to. We then apply these design patterns in the domain of transport. In this domain, we show how software producers, users of the software, and other stakeholders, including individual transport providers, can participate in a Review Alliance Board for the commissioning, production, and review of software platforms for transport systems. The contribution we make is to propose how membership in a Review Alliance Board can be an alternative strategy for both software producers and trade union representatives in taking collective action to assure the quality of workplace software in the context of the growing platform economy.
Keywords: 650; Platform economy; Trade unions; Guilds; Cooperatives; Alliances; Collective action; Transport